Does hsa-miR-223-3p from platelet-derived extracellular vesicles regulate tissue factor expression in monocytic cells?. (3rd October 2022) - Collier, Mary E. W.; Ambrose, Ashley R.; Goodall, Alison H.
Abstract: Extracellular vesicles (EVs) released from activated platelets contain microRNAs, the most abundant of which is hsa-miR-223-3p. Endogenous hsa-miR-223-3p suppresses the expression of tissue factor (TF), the initiator of the extrinsic coagulation pathway, in endothelial cells. Monocytes can be induced to express TF to enhance coagulation, but the role of hsa-miR-223-3p in regulating monocyte TF remains unknown. This study examined whether hsa-miR-223-3p from platelet-derived EVs (pdEVs) affects TF expression in monocytes. THP-1 cells, differentiated into a monocyte-like phenotype with 1α, 25-dihydroxyvitaminD3, were transfected with hsa-miR-223-3p mimic or control microRNA. Alternatively, THP-1 cells were incubated with pdEVs from PAR1-agonist peptide activated-platelets, as platelet releasate, or pdEVs isolated by ultracentrifugation. Transfection with hsa-miR-223-3p mimic resulted in significant reductions in TF protein, determined by western blotting and flow cytometry and reduced procoagulant activity, measured by a TF-specific factor Xa generation assay, compared to cells transfected with control microRNA. This reduction was reversed by co-transfection with hsa-miR-223-3p inhibitor, AntagomiR-223. Incubation of THP-1 cells with pdEVs also decreased TF expression; however, this was not reversed by AntagomiR-223. Taken together, monocyte TF expression is downregulated by hsa-miR-223-3p, but when transferred via pdEVs the effect was not reversed with Antagomir-223, suggesting other pdEV components may contribute to TF regulation. Abbreviations: Tissue factor (TF), Factor VII (FVII), activated Factor VII (FVIIa), Factor X (FX), activated Factor X (FXa), extracellular vesicles (EVs), microvesicles (MVs), platelet-derived extracellular vesicles (pdEVs), protease-activated receptor 1 agonist peptide (PAR1-AP), lipopolysaccharide (LPS), P-selectin glycoprotein ligand-1 (PSGL-1), Tris-Buffered Saline Tween (TBST), room temperature (RT) uf0001